Planning Department Third Five-Year Plan Annual Plan 1965-66 - Planning Commission (Planning Commission, 1965)
Summary Statement of State Plan Outlays For 1965-66 List of Schemes Included in State Plan For 1965-66 List of Centrally Sponsored Schemes Proposed to be Implemented in 1965-66
Planning Department